Analysis of Marketing Strategies in Increasing Competitiveness in MSMEs - Alpiana, Nina; Indah, Djunita Permata; Helmi, Syarieh M. (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Marketing strategy is an important step in achieving sustainable competitive advantage for companies that produce products or services. Increased competition like other small businesses, many face difficulties in building and implementing the right marketing strategy. The variety of problems faced by the company requires a comprehensive plan as a guide in carrying out its activities.  The purpose of the research is to provide an overview of marketing strategies to improve the competitiveness of MSMEs in HAMPA stalls and to determine the effectiveness of the implementation of marketing strategies implemented to improve competitiveness. In this study, researchers used qualitative methods with descriptive data presentation. The data collection methods used in this research are interview, observation, and literature review methods.  From the results of this study using modern marketing strategies generally consists of three main stages, namely market segmentation, target market determination, and market positioning. The concept of mix to improve product competitiveness, price, place and promotion. This research shows that sales have increased due to cooperation with Pontianak city influencers, and decreased due to decreased sales intensity in the month of Ramadan.